2010
DOI: 10.1111/j.1526-4610.2009.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Topiramate Therapy in Patients With Migrainous Vertigo

Abstract: In the overall group, topiramate was found to be effective in reducing the frequency and the severity of vertigo and headache attacks. Both doses of the drug were equally efficacious. The 50 mg/day dose seems to be appropriate as higher adverse effects were noted when 100 mg/day was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…In an investigation by Gode et al, not included in our analysis due to nonevaluable data, reductions in frequency and intensity of headache and vertigo attacks were observed with topiramate use after 24 weeks. 46 However, its use was limited by side effects: paresthesia (19/30), fatigue (11/30), memory/concentration issues (8/30), decreased appetite (14/30), and weight loss (4/30). Four patients discontinued treatment in this study due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation by Gode et al, not included in our analysis due to nonevaluable data, reductions in frequency and intensity of headache and vertigo attacks were observed with topiramate use after 24 weeks. 46 However, its use was limited by side effects: paresthesia (19/30), fatigue (11/30), memory/concentration issues (8/30), decreased appetite (14/30), and weight loss (4/30). Four patients discontinued treatment in this study due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Abortive therapy using antimigraine medications like triptans and antiemetics such as promethazine and meclizine has been thought to be helpful [28,29]. Prophylactic therapy involves using anti-migraine medications with anecdotal preference for verapamil, topiramate, and lamotrigine [29,30]. A recent study showed significantly increased benefit in the treatment of vertigo in vestibular migraine patients using flunarizine in addition to betahistine, a finding that supports the role of calcium channel dysregulation in the pathogenesis of vestibular migraine [31].…”
Section: Vestibular Migrainementioning
confidence: 95%
“…A recent noncontrolled open study suggests that topiramate could also be effective for the preventive treatment of migrainous vertigo, even at a small dose of 50 mg/day [34 ]. In the large INTREPID study, topiramate 100 mg/day was unable to prevent the development of chronic daily headache in migraineurs with high frequency of attacks, although it was effective in reducing overall headache days [35 ].…”
Section: Pharmacological Treatmentmentioning
confidence: 97%